Delayed auditory pathway maturation in the differential diagnosis of hypoacusis in young children (2008)
Auditory deficiencies have profound implications for the development of communication abilities, social exchange, and cognitive skills. Although advances in technological instrumentation have decreased the age at which it is possible to detect auditory deficits, an absence of electrophysiological or behavioral reaction to sound does not always reflect hypoacusis. The objective of this study was to evaluate the evolution of audition in a group of children referred for therapy to the CINDA Foundation (Center for Research and Information in Auditory Deficiencies) in Bogota, Colombia, with an initial diagnosis of severe to profound sensorineural hearing loss. We evaluated 25 patients younger than 2.5 years of age with a protocol which included auditory evoked potentials, behavioral responses (tonal audiometry-responses to voice and startle) and language observation. After evaluation, the children began a program of auditory stimulation with audiological follow-up for a period of 6 months to 1 year. The audiological follow-up of the children after auditory stimulation showed significant improvements in both electrophysiological and behavioral indices of their hearing levels (p less than .001, one-tailed Wilcoxon exact test). We found a high percentage of children in early stages of auditory maturation with a false diagnosis of hypoacusis (32%). The absence of response may result from compromised auditory reception or processing. Thus, delayed maturation of the auditory pathway should be considered in the differential diagnosis of young children with sensorineural hearing loss. © 2007 Elsevier Ireland Ltd. All rights reserved.